2015
DOI: 10.1039/c4ra11999a
|View full text |Cite
|
Sign up to set email alerts
|

A novel sorbent for lanthanide adsorption based on tetraoctyldiglycolamide, modified carbon inverse opals

Abstract: Carbon inverse opals (C-IOP) were noncovalently modified with tetraoctyldiglycolamide (TODGA). The effect of HNO 3 concentration in the aqueous phase and that of the TODGA concentration in the sorbent phase on the adsorption of microquantities of Y, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb and Lu nitrates from HNO 3 solutions by CIOP modified with TODGA was considered. The stoichiometry of the sorbed complexes has been determined by the slope analysis method. The efficiency of lanthanides(III) adsorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…The maximum capacity of our materials can be compared to the literature. Turanov et al 15 obtained a capacity of 18 mg g −1 for Eu in a 3 M HNO 3 matrix with a DGA impregnated on porous carbon (inverse opal), but impregnated ligands tend to exhibit lower capacity upon cycling. Fan et al 48 observed a capacity of 55.56 mg g −1 for Eu with humeric acid grafted on carbon nanotubes at pH 4.5, a medium 2 orders of magnitude more alkaline than that used in this study.…”
Section: Ph Variation Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The maximum capacity of our materials can be compared to the literature. Turanov et al 15 obtained a capacity of 18 mg g −1 for Eu in a 3 M HNO 3 matrix with a DGA impregnated on porous carbon (inverse opal), but impregnated ligands tend to exhibit lower capacity upon cycling. Fan et al 48 observed a capacity of 55.56 mg g −1 for Eu with humeric acid grafted on carbon nanotubes at pH 4.5, a medium 2 orders of magnitude more alkaline than that used in this study.…”
Section: Ph Variation Studymentioning
confidence: 99%
“…Yet, one of the most important challenges with OMC used as solid-phase for SLE is the proper control of the surface modification. Previous attempts have shown the possibility to use DGA-type ligand-modified carbon nanotubes and porous carbon to extract lanthanides or actinides in aqueous solution. , As highlighted in Table , published articles using carbon-based adsorbents for lanthanide extraction have focused on one or two elements instead of assessing the separation behavior for all Ln. In addition, the conditions used to evaluate the adsorption performances of these materials are often in pH conditions much higher than those used in industrial settings.…”
Section: Introductionmentioning
confidence: 99%
“…Much of the research work on Sc(III) recovery by adsorption and extraction has been performed with resins, [10][11][12][13] 17 or extractants impregnated onto a solid support. [18][19][20][21] Ionic liquids (ILs) show a great potential for application in hydrometallurgy, both solvent extraction [22][23][24] and leaching.…”
Section: Introductionmentioning
confidence: 99%
“…However, large inventories of diluents and modifiers were used in solvent extraction, thereby leading to severe environmental problems . Various techniques based on adsorption, such as polymeric composite bead, magnetic nanomaterial, hybrid material, , modified carbon inverse opal, were developed to restrict the hazardous impacts of volatile organic compounds. The advantages of adsorption, that is, simplicity, flexibility, cost effectiveness, ease of operation, and lower consumption of hazardous reagent (no hazardous diluent is used), make it a competitive alternative to solvent extraction …”
Section: Introductionmentioning
confidence: 99%